GAYA HIDUP DAN STATUS KESEHATAN SOPIR BUS SUMBER ALAM DI KABUPATEN PURWOREJO, JAWA TENGAH - Kartika Musbyarini; Faisal Anwar; Cesilia Meti Dwiriani (Jurnal Gizi dan Pangan, 2010)
The general objective of this research was to analyze the correlation between life style with health status of Sumber Alam’s Drivers in Purworejo District, Central Java. The research was conducted using cross sectional study design from July throughAugust 2009 in PO Sumber Alam Purworejo District.Sample was chosen by simple random sampling which resulted67drivers. Almost all the samples (91%) had smoking habit and all of the samples had no habit on alcohol drinking. More than half (58.2%) had excersice habit. The physical activity levels in work day was higher than that in holiday  (p<0.05). More than half samples (67.2%) eat rice three times a day. Tempeh was popular side dishes consumed by almost all samples more than three times a week. Egg was consumed by almost half samples once until three times a week. Generally, intake of vegetables, fruits and milk was still low, as well as intake of food that have high risk for degenerative disease. The nutritional status of samples ranged from underweight to obesity, with more than half categorized as normal nutritional status. For the last one month, there were 7.5% samples suffered for degenerative diseases, 20.9% for infectious diseases and 16.4% for non infectious disease.